A UTILIZAÇÃO DO COMPUTADOR E DA INTERNET NA FACILITAÇÃO DO PROCESSO DE APRENDIZAGEM SIGNIFICATIVA DE CONTEÚDOS DE CIÊNCIAS NATURAIS - Felicetti, Suelen Aparecida (2016)
The today's society counts with a diversity of information and communication technologies (ICT), that facilitate the production, obtainment and sharing of information at global levels. They are understood as equipment that allow to processing information and the comunication. In the school stand out the computer and the internet, because they provide to teachers and students quick and easy access to diverse content, they motivate for learning, and they provide resources and tools to help at the teaching and learning processes. They are sought ways and methodologies for that the insertion and the use of these resources on the teaching of natural sciences happens inherently and effectively, enabling the meaningful learning (ML) of the elementary school students. So, the objective of this research was to promote the meaningful learning of the astronomy concepts in a 9th class, using the computer and the internet. For this, the main proposal was that students make research works on websites about some basic astronomy concepts, formulating and socializing a final written work, which consider the conclusions of them and demonstrate their conceptual assimilation. In addition to these research, the students answered questionnaires, discussed collectively about the astronomy concepts and prepared oral presentations about their research, being that these activities, along with the perceptions of the whole educational process, served as analytical tools. The planning of this proposal as a whole compose the educational object of this research, that consists of a didactic material to help on the schoolar research proposition about astronomy, for students in the 9th grade of elementary school. It was realised that the methodology used helped the students to become more autonomous individuals, conscious and active at the teaching and learning process. Still, the most part of students were willing to participate and to learn, which contributed, along with potentially significant material developed, to realize that conceptual evolution about some concepts of astronomy, which suggests that the process has been significant. Such observations dialogue with points that are proposed in the literature, about how promising might be the use of the computer and the internet at school, about the inclusion of students in the context of scholar research and about the importance of the learning to be significant.